Pemberdayaan Masyarakat Melalui Pengembangan Desa Wisata Nglingo dalam Mendukung Kulon Progo The Jewel Of Java - Sahabudin Sidiq; Yulianto Purwono (Asian Journal of Innovation and Entrepreneurship, 2017)
Yogyakarta is one of the most popular tourist destinations by tourists to spend their vacation time, it can be seen from the dense visit of the tourists who come during the holidays. The lack of facilities and infrastructure in Yogyakarta City to respond to the high tourists make new problems arise. This makes some tourists look for some alternative new tourist areas, such as natural attractions in the suburbs, namely in Gunung Kidul, Sleman and Kulon progo.Hamlet Nglinggo included as one of the tourist village in Special Region of Yogyakarta which is located Samigaluh, Kulon progo. Nglinggo tourist village is a new tourist village and is busy visiting tourists in recent years. This tourist village offers natural attractions tea plantations and waterfall Curug Watu Jonggol which is still one village with the existence of tea plantations. The potential of natural tourism is the main attraction compared to other tourist villages in Yogyakarta. Based on the data of the village tourist managers, the average number of visits per month reached the number of visits 1000-1500 the number of visitors (source pokdarwis). Increasing the number of visits to make the latest problems resulting from the absence of planning in the development of tourist villages, low human resources, and institutional governance is not good to cause some of the potential of this tourist village is less managed and competitive.Based on the problems mentioned above then in need of community empowerment efforts through the development of Nglingo Tourism Village so as to support slogan kabuapten Kulon progo the Jewel of Java. The goal is the creation of tourism village development through participatory planning, creation of institutional governance, and human resource capacity building. The methods used are training, mentoring, and implentation. While Partners cooperation in pelasakanaan KKN-PPM is the village government Pagerharjo District Samigaluh Kulonprogo.